Pelatihan Edukasi Macam-Macam Tindak Kejahatan Teknologi Informasi (Cyber Crime) Dunia Maya dan Penanganannya - Sovina, Mutiara; Harahap, Faisal Amir; Lazuly, Ivi; Khalid, Mhd. Azmi (LPPM Universitas Potensi Utama, 2024)
Educational training regarding information technology crime (cyber crime) and its handling is an important step in facing increasingly complex cyber threats. This article discusses the types of cyber crime, its impact, as well as effective handling strategies and methods. This research uses observation methods through community service carried out at SMKS Bina Satria Medan, literature studies and mixed methods. This research uses a qualitative approach with case study methods at several institutions that have implemented this training. The results of this research show an increase in participants' awareness and ability to identify and deal with cyber crime.